Stabilisation of Large Scale Spoil Piles in Deep Open Strip Coal Mines - Boyd G; Eckersley J (The Australasian Institute of Mining and Metallurgy, 1981)
A brief review is presented of the mechanisms and causes of spoil pile failures which have occurred at the Goonyella Mine. In particular, the results of a recent geo- technical investigation of the spoil dumps in the Cleanskin pit are briefly presented. Spoil pile hydrology is discussed in relation to the use of effective stress concepts in the analysis of spoil pile stability. Experience in relation to stabilisation of dragline dumps is discussed as well as the likelihood of current techniques being success- ful in the prevention of gross failures if prestrip material is placed in existing spoil piles. Parameters exerting a major control on dump stability are outlined.